2016
DOI: 10.1136/acupmed-2015-010981
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture and Cognitive Behavioural Therapy for Sub-Syndromal Depression among Undergraduates: A Controlled Clinical Trial

Abstract: BackgroundIndividuals with sub-syndromal depression (SSD) are at increased risk of incident depressive disorders; however, the ideal therapeutic approach to SSD remains unknown.ObjectiveTo evaluate the effects of electroacupuncture (EA) and cognitive behavioural therapy (CBT), alone or in combination, on depressive symptoms.MethodsUndergraduate students with SSD were recruited and allocated to one of four groups based on their preferences: EA (n=6), CBT (n=10), EA+CBT (n=6), and untreated control (n=11) groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…This gives the patients an acupuncture effect and electricity stimulation simultaneously. Recently, many studies have been performed to evaluate EA and the results generally showed efficacy and safety [8] for neurological diseases such as MCI [9], schizophrenia [10], vascular dementia [11, 12], stroke [13], depressive symptoms [14], Parkinson’s disease [15], and Alzheimer’s disease [16]. However, a systematical review of studies on MCI has not been performed to date.…”
Section: Introductionmentioning
confidence: 99%
“…This gives the patients an acupuncture effect and electricity stimulation simultaneously. Recently, many studies have been performed to evaluate EA and the results generally showed efficacy and safety [8] for neurological diseases such as MCI [9], schizophrenia [10], vascular dementia [11, 12], stroke [13], depressive symptoms [14], Parkinson’s disease [15], and Alzheimer’s disease [16]. However, a systematical review of studies on MCI has not been performed to date.…”
Section: Introductionmentioning
confidence: 99%
“…As a modern therapeutic practice of CAM, electroacupuncture (EA) combines standard acupuncture with a gentle electrical current to stimulate acupuncture points. EA has been used successfully to treat depression in China and several other countries worldwide for its efficiency and minimal adverse effects (Ulett et al, 1998 ; Kim et al, 2013 ; Guo et al, 2016 ; Schroeder et al, 2017 ). Previous clinical and preclinical studies have showed that EA relieved depressive-like behavior in patients with depression and animal models (Ulett et al, 1998 ; Duan et al, 2016 ; Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…EA has been widely used to treat different psychiatric conditions, including depressive disorder (43). The putative antidepressant actions of EA are believed to involve modulation of hormones, neurotransmitters, and/or cytokines (25). Le et al also found that EA could regulate the hypothalamus-pituitary-adrenal cortex axis, influence the hippocampus, and affect the dopaminergic and/or serotonergic systems to exert antidepressive activity (44).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study found that depression is the second most common of the most commonly treated acupuncture indications in the United States (24). A single-center controlled trial of subthreshold depression found that EA, counseling, and EA + counseling could significantly improve HAMD-17 scores, Center for Epidemiologic Depression scale, and WHO Quality of Life-Brief version scores of undergraduates students, and the remission rate is higher than that of the control group (p<0.05) (25). However, the clinical value of this finding is limited because it is a single-center clinical trial with a small sample size.…”
Section: Introductionmentioning
confidence: 99%